High density lipoprotein and metabolic disease: Potential benefits of restoring its functional properties - Teja Klancic; Lavinia Woodward; Susanna M. Hofmann; Edward A. Fisher (Elsevier, 2016)
Background: High density lipoproteins (HDLs) are thought to be atheroprotective and to reduce the risk of cardiovascular disease (CVD). Besides their antioxidant, antithrombotic, anti-inflammatory, anti-apoptotic properties in the vasculature, HDLs also improve glucose metabolism in skeletal muscle. Scope of the review: Herein, we review the functional role of HDLs to improve metabolic disorders, especially those involving insulin resistance and to induce regression of CVD with a particular focus on current pharmacological treatment options as well as lifestyle interventions, particularly exercise. Major conclusions: Functional properties of HDLs continue to be considered important mediators to reverse metabolic dysfunction and to regress atherosclerotic cardiovascular disease. Lifestyle changes are often recommended to reduce the risk of CVD, with exercise being one of the most important of these. Understanding how exercise improves HDL function will likely lead to new approaches to battle the expanding burden of obesity and the metabolic syndrome. Keywords: High density lipoprotein (HDL), Metabolic disease, Glucose homeostasis, Physical activity, Atherosclerotic plaque regression, HDL function